Arabisasi sebagai Modernisasi Bahasa Arab dan Semangat Nasionalisme - Umi Kulsum (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
Abstract Arabization is a linguistic phenomenon that occurs in Arabic in the form of word formation in Arabic originating from a foreign language. This study aims to reveal this phenomenon and its function as a form of modernizing the Arabic language and the spirit of nationalism among Arabs. This research is a qualitative-descriptive research with data in the form of articles, books, newspapers, and dictionaries. The data collection technique used is the listening and note-taking technique. While the data analysis techniques in the form of organizing, sorting, and synthesizing data. The results of the study show that arabization is a necessity for the Arabic language that continues to develop. Arabization is not a weakness, but it strengthens the nature of language, namely growing and developing. Arabization is also considered a form of modernization of the Arabic language and the spirit of nationalism among Arabs. Keyword: Arabization, Language Modernization, Spirit of Nationalism